Sample Productivity and Cost Estimates of Producing Longan (Dimocarpus longan Lour.) in South Florida. - Fredy H. Ballen; Edward Evans; Aditya Singh; Jonathan H. Crane (EDIS)
Interest is growing in minor tropical fruit crops. This 6-page publication written by Fredy H. Ballen, Edward A. Evans, Aditya Singh, and Jonathan H. Crane and published by the UF/IFAS Food and Resource Economics Department provides an estimate of the costs and returns associated with the operation of an established longan grove in south Florida. Information presented in this article was obtained through field interviews with growers and industry experts; it reflects a wide variety of production practices in small longan orchards of 1 to 4 acres and should help estimate the financial requirements of operating an established grove. http://edis.ifas.ufl.edu/fe1049